Yeast populations associated with Ghanaian cocoa fermentations analysed using denaturing gradient gel electrophoresis (DGGE) - Nielsen, D.S.; Hønholt, S.; Tano-Debrah, K.; Jespersen, L. (Yeast, 2005)
The yeast populations associated with the fermentation of Ghanaian cocoa were investigated using denaturing gradient gel electrophoresis (DGGE). Samples were collected at 12-24 h intervals from heap and tray fermentations, at three different fermentation sites and different periods during the season. Eukaryotic universal primers were used to amplify a fragment of the 26S rRNA gene. The DGGE profiles were relatively complex, underlining that the fermentation of cocoa is a complex microbial process. The identities of selected fragments in the denaturing gels were revealed by sequencing. Hanseniaspora guilliermondii, Candida krusei and Pichia membranifaciens were detected from most fermentations, indicating their possible important role in the fermentation of Ghanaian cocoa. Saccharomyces cerevisiae and Candida zemplinina were almost exclusively detected during tray fermentations. The developed DGGE protocol was compared with traditional culture-based isolations. The results were comparable but slightly different, as one yeast species (C. zemplinina) was only detected using DGGE. On the other hand, Trichosporon asahii yielded only faint bands in the denaturing gels, despite the fact that it was detected using culture-based methods. Analysis of pure cultures showed that the targeted region of the 26S rRNA gene was poorly amplified in T. asahii, whereas all other investigated isolates were amplified efficiently using the chosen PCR approach. Cluster analysis revealed that the DGGE profiles clustered according to fermentation method and fermentation site. Furthermore, clustering according to progress in the fermentation was observed. The DGGE technique therefore seems to offer a relatively fast and reliable method for studying yeast population dynamics during cocoa fermentations. The nucleotide sequences determined in this study have been assigned Genbank Accession Nos AY762330-AY762349. Copyright © 2005 John Wiley & Sons, Ltd.
Keywords: 26S rRNA gene; Cluster analysis; Cocoa; DGGE; DNA extraction; Fermentation; Yeast